Effects of Microwave and Infrared + Microwave Drying of Wood Materials on Energy Consumption, Water Absorption, and Mechanical Properties - Burcin Saltik (BioResources, 2024)
The objective of this study was to shorten the drying time of wood material using microwave and infrared + microwave drying methods, compare the energy assumption, analyze their improvement in water absorption, and compare the compression strength perpendicular and parallel to fibers. Red pine (Pinus brutia) and Eastern spruce (Picea orientalis) woods were prepared in three groups. The first group was oven dried, the second group was dried by microwave, and the third group was dried by infrared + microwave methods. The analysis results for energy consumption, moisture content, and compression strength perpendicular and parallel to the fibers were performed. Compression strengths were determined with a universal testing device. According to the results obtained, with 15 min microwave drying, 4% moisture content was reached in the wood samples and both time and energy were saved. It was observed that oven drying consumed 93% more energy than 15 min microwave drying. Samples dried with infrared 30 s + microwave 5 min had higher compression strength in the direction perpendicular to the fibers and samples dried with microwave for 5 min had higher compression strength in the direction parallel to the fibers.